2002
DOI: 10.1016/s0022-5347(05)65092-6
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Patient Dissatisfaction After a Tension-Free Vaginal Tape Procedure for Urinary Incontinence

Abstract: These results confirm that the tension-free vaginal tape procedure is associated with a high objective but lower subjective cure rate. The procedure performed using local anesthesia was associated with a lower incidence of difficult voiding and new onset urge symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
0
4

Year Published

2003
2003
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(35 citation statements)
references
References 13 publications
5
26
0
4
Order By: Relevance
“…It was 20.2% in the current study and this is comparable with 21.3% reported by Deval et al [2]. Although Botros et al reported that the rate of de novo subjective urge urinary incontinence for TVT was significantly higher than that of Monarc and Sparc, [5] these differences were not found in the current study.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…It was 20.2% in the current study and this is comparable with 21.3% reported by Deval et al [2]. Although Botros et al reported that the rate of de novo subjective urge urinary incontinence for TVT was significantly higher than that of Monarc and Sparc, [5] these differences were not found in the current study.…”
Section: Discussionsupporting
confidence: 83%
“…This issue has been rarely ever reported other than by Deval et al, Falconer et al, and Botros et al. They briefly hypothesized that the changes in paraurethral collagen metabolism or sclerosis around the sling, or the effect position of the sling may elicit the new onset of urge symptoms [2,3,5].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, in this study lower subjective cure rates were obtained in women with mixed incontinence [11]. The same study also revealed that subjective cure rate was not affected by any other preoperative features of patient characteristics, including patient age.…”
Section: Discussionsupporting
confidence: 73%
“…Urinary retention was found to be between 2.3-13% in various series [7,10,11,17,18,19,20]. Spontaneous voiding with insignificant residuals was achieved in most of the patients within 2 weeks in these series.…”
Section: Discussionmentioning
confidence: 69%